Ubiquity of microplastics in the surface waters and sediments sampled for five identified river mouths of Manila Bay - Osorio, Ezra D.
Microplastics have been increasingly documented globally in numerous environmental compartments including in the marine and freshwater systems, and these are considered to be an emerging contaminant due to the growing concerns to their environmental and health impacts. However, little information exists in the Philippines despite the fact that the country is considered to be the third largest contributor of plastics in oceans. Hence, this study is the first to evaluate the abundance, distribution, and composition of microplastic pollution in Manila Bay, specifically in the mouths of five rivers (Cañas River, Meycauayan River, Parañaque River, Pasig River and Tullahan River) draining into the bay. Surface water and sediments samples were collected, then passed through a stacked sieves with sizes of 2.36mm, 1mm, 0.5 mm, 0.125 mm and 0.075 mm. These samples were digested to remove organic matter, and salt solutions were added to allow the microplastics to float. Particles were extracted using peristaltic pump, examined under a 40x magnification stereo microscope, and quantified and categorized into size, color, and type. Results show that microplastics were present ubiquitously at the surface waters and sediments of all river mouths, but with varying concentration of 1,580 to 57,665 particles/m³ (surface water) and 386 to 1,357 particles/kg (sediment). Based on the categorization according to shape, color, and size, fragment was the most abundant shape, while white, blue and transparent were the most prevalent colors. Fourier Transform Infrared Spectroscopy (FTIR) analysis revealed that polypropylene, high and low-density polyethylene and polystyrene were the main types of microplastics present in the river mouths. This study can provide valuable points of reference to better understanding microplastic pollution and coastal systems, and the results verify that higher levels of human impact lead to greater plastic pollutio